Screening of macromolecular cross-linkers and food-grade additives for enhancement of catalytic performance of MNP-CLEA-lipase of Hevea brasiliensis - Ab Aziz Al Safi, Nur Amalin; Yusof, Faridah (2020)
Skim latex from Hevea brasiliensis (rubber tree) consist of many useful proteins and enzymes that can be utilized to produce value added products for industrial purposes. Lipase recovered from skim latex serum was immobilized via cross-linked enzyme aggregates (CLEA) technology, while supported by magnetic nanoparticles for properties enhancement, termed ‘Magnetic Nanoparticles CLEA-lipase’ (MNP-CLEA-lipase). MNP-CLEA-lipase was prepared by chemical cross-linking of enzyme aggregates with amino functionalized magnetic nanoparticles. Instead of using glutaraldehyde as cross-linking agent, green, non-toxic and renewable macromolecular cross-linkers (dextran, chitosan, gum Arabic and pectin) were screened and the best alternative based on highest residual activity was chosen for further analysis. Same goes for additives; the traditional use of expensive BSA was replaced with low cost, food grade additives (egg protein, soy protein and milk protein). The optimum condition parameters such as concentration of cross-linker, concentration of additive and concentration of precipitant were determined using one factor at a time (OFAT) method and structural analysis was done by FTIR. The screening results showed that pectin was the best cross-linker (118 % residual activity) and soy protein was the best additive (129 % residual activity) for MNP-CLEA-lipase with optimum conditions of 180 mg/ml pectin, 0.6 % w/v soy protein and 80 % saturation ammonium sulphate. FTIR of MNP-CLEA-lipase showed an Amide I and Amide V bands which originated from silanized magnetic nanoparticles (MNP) and a new band, Amide II was formed prior to the successful CLEA immobilization of lipase enzyme with MNPs